Pengaruh Variasi Massa Raw Material dan Jenis Material Terhadap Respon Steady State Error Spindle Mesin Lathe Mini - Muhammad Ali Masykur; Ahmad Anas Arifin; Desmas Arifianto Patriawan (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
Lathe machines have played an important role in the development of the world of education and industry, learning how to operate lathe machines also requires expertise in accuracy, accuracy, speed, and improving quality and producing maximum results, this research method focuses on the analysis of motor spindle rpm and motor response mini lathe machine when given variations in load, material and feed, namely variations in spindle speed of 1000, 2000 and 3000 Rpm, mass of raw material Teflon PL and Aluminum 50, 100 and 150 grams, feeding 0.5 mm. The results of the study were to The greatest steady state error averagely was to 8 volt by 2000 rpm; it situation was obtained at no feeding procedure at a voltage of 8 volts with a target of 2000 rpm, without feeding conditions. Further, the feeding depth 0.5mm was obtained the greatest steady state error at 4 volt and 1000 rpm.Keywords: Lathe, Steady State Response, Spindle Speed